Foodborne Infections and Intoxications in Hyderabad India. (13th February 2014) - Sudershan, R. V.; Naveen Kumar, R.; Kashinath, L.; Bhaskar, V.; Polasa, K.
Abstract : Foodborne diseases are one of the health hazards and causes of morbidity and mortality in developing countries. In India there are no systematic studies to understand the types of foods involved and the etiological agent causing the disease. Therefore, a pilot study was proposed to investigate the food poisoning cases, undertaken by the Ronald Ross Institute of Tropical Diseases, which is a referral hospital for foodborne diseases in Hyderabad. Food and stool/rectal swabs of the patients affected were collected for microbiological examination. Odds ratio and 95% confidence interval were used to express the statistical significance of the differences. Epidemiological, environmental, and laboratory components indicated that Staphylococcus aureus was the etiological agent in most of the cases and in one case Salmonella spp. were the main cause of food poisoning. This study indicated the need to take up foodborne disease surveillance under the Indian context and to identify the common high-risk food commodities for microbial contamination and identification.